Liver Cirrhosis: Evaluation, Nutritional Status, and Prognosis - Hiroki Nishikawa; Yukio Osaki (Mediators of Inflammation)
The liver is the major organ for the metabolism of three major nutrients: protein, fat, and carbohydrate. Chronic hepatitis C virus infection is the major cause of chronic liver disease. Liver cirrhosis (LC) results from different mechanisms of liver injury that lead to necroinflammation and fibrosis. LC has been seen to be not a single disease entity but one that can be graded into distinct clinical stages related to clinical outcome. Several noninvasive methods have been developed for assessing liver fibrosis and these methods have been used for predicting prognosis in patients with LC. On the other hand, subjects with LC often have protein-energy malnutrition (PEM) and poor physical activity. These conditions often result in sarcopenia, which is the loss of skeletal muscle volume and increased muscle weakness. Recent studies have demonstrated that PEM and sarcopenia are predictive factors for poorer survival in patients with LC. Based on these backgrounds, several methods for evaluating nutritional status in patients with chronic liver disease have been developed and they have been preferably used in the clinical field practice. In this review, we will summarize the current knowledge in the field of LC from the viewpoints of diagnostic method, nutritional status, and clinical outcomes.